Issues on the Impact of Migration on the Labour Market and the Role of National Employment Agency in the Integration of Returned Migrants in the Republic of Moldova - Raisa DOGARU (Eastern European Journal of Regional Studies, 2021)
Abstract: For the Republic of Moldova, international labour migration is an important factor in overcoming imbalances both in the labour market and in the national economy. International labour migration, through its transfers, contributes to economic growth and the combating poverty. At the same time, labour migration generates certain economic and social risks related, first of all, to the aging population and the increase of the labour force deficit on the labour market. One solution to overcoming these risks would be to stimulate return migration and the integration of returned migrants into employment, an activity that is the responsibility of the National Employment Agency. The analysis of the impact of labour migration on the national economy and the labour market, as well as the role of the Employment Agency in the process of integration of returned migrants is the object of study of this article.